Improving Citizen Satisfaction in Dukuh Menanggal: A Six Sigma-Based Quality Enchancehement Strategy - Alfany, Mochammad Zulfikar; Zunaidi, Rizqa Amelia (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
This study aims to identify the service quality in Dukuh Menanggal Subdistrict, Surabaya City, explicitly focusing on population registration, correspondence, and social assistance management. The Six Sigma method is employed to initiate improvements in public services. Six Sigma is a quality management system that emphasizes customer satisfaction by measuring the Sigma Quality Level. The analysis is conducted through the DMAIC framework (define, measure, analyze, improve, and control). Data is collected by distributing questionnaires to members of the community who are users of public services in the Subdistrict. The research findings are expected to assist Dukuh Menanggal Subdistrict in considering the proposed improvements put forth by the researchers as initial steps toward better service provision. By implementing the Six Sigma approach, the Subdistrict can enhance service quality, resulting in increased satisfaction and trust among the public regarding the provided public services. This study provides valuable insights into applying the Six Sigma methodology in local governance and its potential to improve service quality, ultimately benefiting the community and the local administration.